Determining Structure‐Activity Relationships in Oxide Derived CuSn Catalysts During CO2 Electroreduction Using X‐Ray Spectroscopy. Issue 5 (24th December 2021) - Pardo Pérez, Laura C.; Arndt, Alexander; Stojkovikj, Sasho; Ahmet, Ibbi Y.; Arens, Joshua T.; Dattila, Federico; Wendt, Robert; Guilherme Buzanich, Ana; Radtke, Martin; Davies, Veronica; Höflich, Katja; Köhnen, Eike; et al.
Abstract: The development of earth‐abundant catalysts for selective electrochemical CO2 conversion is a central challenge. CuSn bimetallic catalysts can yield selective CO2 reduction toward either CO or formate. This study presents oxide‐derived CuSn catalysts tunable for either product and seeks to understand the synergetic effects between Cu and Sn causing these selectivity trends. The materials undergo significant transformations under CO2 reduction conditions, and their dynamic bulk and surface structures are revealed by correlating observations from multiple methods—X‐ray absorption spectroscopy for in situ study, and quasi in situ X‐ray photoelectron spectroscopy for surface sensitivity. For both types of catalysts, Cu transforms to metallic Cu 0 under reaction conditions. However, the Sn speciation and content differ significantly between the catalyst types: the CO‐selective catalysts exhibit a surface Sn content of 13 at. % predominantly present as oxidized Sn, while the formate‐selective catalysts display an Sn content of ≈70 at. % consisting of both metallic Sn 0 and Sn oxide species. Density functional theory simulations suggest that Sn δ+ sites weaken CO adsorption, thereby enhancing CO selectivity, while Sn 0 sites hinder H adsorption and promote formate production. This study reveals the complex dependence of catalyst structure, composition, and speciation with electrochemical bias in bimetallic Cu catalysts. Abstract : A combination of X‐ray spectroscopy methods, electron microscopy, and density functional theory help unravel the origins of selectivity in tunable CuSn based catalysts for electrochemical CO2 conversion to either CO or HCOO − .